Analisis Kinerja Keuangan Berdasarkan Ratio dan Dupont System - Widarnaka, Widarnaka; Mubarak, Kautsar; Parapat, Rosiati; Nofryanti, Nofryanti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
Financial statements to be vital to the passage of a company today. The financial statements can be a source of information and be used to make decisions for each financial statement users. Companies as legal entities in Indonesia have an obligation to build the country's economy, paying taxes is one form of contribution. The purpose of this study was to determine the soundness of the financial performance of TELKOM GROUP. The scope of this study is limited by state decree No.100/MBU/2002, du pont system analysis and payment of income tax. This research was conducted on our financial statements TELKOM GROUP 2018, 2019, 2020, 2021 and 2022 with qualitative descriptive methods. The data were processed using the method of financial ratios required by Ministerial Decree No.10/MBU/2002 SOEs and du pont system analysis. From the processing of our financial ratios GROUP earn a score of 62 points, 60.5 points, 60.5 points, 61 points, and 61 points in 2018, 2019, 2020, 2021 and 2022, respectively. Based on du pont system analysis The GROUP obtained ROE of 23%, 23%, 25%, 25%, and 20% in 2018, 2019, 2020, 2021 and 2022, respectively. These results indicate that our financial soundness GROUP is in a healthy positionKeywords: Financial Statements; financial statement analysis; the level of health; financial ratios